Changing Dynamics of Good Governance in Africa - Wani, Hilal Ahmad; Suwirta, Andi (EDUCARE, 2015)
ABSTRACT: The desire for freedom and justice, the political fallouts from the structural adjustment programmes, and the entrenched autocratic and repressive political institutions dominant in the most of the parts of Africa. Since 1980s, Africa has been in the process of establishing the principles of good governance for making African institutions and authorities accountable enough to run their own state affairs. Research shows that the continent has made some progress in this area, but more still needs to be achieved. Â In this paper, we will examine the recent developments in the field of good governance and consider what is still needed in order to achieve a prosperous and progressive Africa. The research data has been taken from UNDP (United Nations Development Programme), AU (African Union), UNCTAD (United Nations Conference on Trade and Development), WB (World Bank), UNESCO (United Nations on Education, Scientific, and Cultural Organization), and AfDB (African Development Bank) research reports. We have tried to highlight the positive aspects of recent developments, and also the transitional aspect of good governance in the African continent. We have also tried to avoid negative dimensions on the basis research data, which definitely shows over the last two decades Africa has made real progress and is still moving towards sustainable development, effective governance, and stable growth. And it is also predicted, at some time in the near future, Africa will have achieved significant growth and economic progress, and will have effective political institutions and better leaders.Â KEY WORDS: Good governance, changing dynamics, African continent, sustainable development, stable growth in economic, and better political prospect.Â Â About the Authors: Dr. Hilal Ahmad Wani is an Assistant Professor at the Department of Political Science and Strategic Studies, College of Law and Governance MU (Mekelle University) in Mekelle, Tigray, Ethiopia; and Andi Suwirta, M.Hum. is a Senior Lecturer at the Department of History Education UPI (Indonesia University of Education) in Bandung, West Java, Indonesia. Corresponding authors are: wanihilal@gmail.com and andisuwirta@yahoo.com Â How to cite this article? Wani, Hilal Ahmad & Andi Suwirta. (2015). âChanging Dynamics of Good Governance in Africaâ in EDUCARE: International Journal for Educational Studies, Vol.7(2) February, pp.189-202. Bandung, Indonesia: Minda Masagi Press and UMP Purwokerto, ISSN 1979-7877. Chronicle of the article: Accepted (January 17, 2015); Revised (January 29, 2015); and Published (February 28, 2015).